The Fennoscandian Shield deep terrestrial virosphere suggests slow motion ‘boom and burst’ cycles - Karin Holmfeldt (Nature Portfolio, 2021)
Karin Holmfeldt et al. sequence metagenomes and metatranscriptomes of viruses in deep groundwaters down to 448 m below the surface. The results reveal ecological dynamics of viruses including slow motion ‘boom and burst’ cycles and a ‘kill the winner’ model potentially driven by viral predation.